Development of e-LKPD biology concept to improve students critical thinking skills - Ardela Anggereni; Aminuddin Prahatama Putra; Atiek Winarti (JPBIO (Jurnal Pendidikan Biologi), 2022)
The development of electronic LKPD is an alternative innovation to meet the need for teaching materials that can prepare decisivereasoning. The reason for this study was to create the practicality and effectiveness of the e-LKPD concepts of Biology Science in SMP class VIII which were developed to train critical thinking skills. This investigation a Developmental navorsing study use written questions attached the Tessmer method. Improvement stages incorporate self assessment, master audit, individual test, little gathering test and ground test. The navorsing location for validity testing is at Lambung Mangkurat University, while practicality and effectiveness tests are carried out at MTsN 3 Hulu Sungai Tengah. The exploration persons were 3 learner for the singular test, 7 learner for the little gatheringtest and 20 learner for the ground test. Results the showed that the developed e-LKPD the practicality of the e-LKPD shows very practical criteria to be reviewed from the student's response indicating the models for unequivocally concurring ith the reasonableness of the e-LKPD in practicing decisive reasoning. Effectiveness of developed the e-LKPD is declared effective for training decisive reasoning abilities and understudy learning result are named high as seen from  N-Gain the score